Q221K mutation in VP2 drives antigenic shift of infectious bursal disease virus - Xiong, Haifeng; Wu, Jiayan; Xie, Quan; Li, Tuofan; Wan, Zhimin; Qin, Aijian; Ye, Jianqiang; Shao, Hongxia (Frontiers in Immunology, 2025)
IntroductionInfectious bursal disease (IBD) is a severe immunosuppressive disease caused by the infection of infectious bursal disease virus (IBDV) in chicken. Recently, an emerging mutant named novel variant IBDV (nVarIBDV) has rapidly spread in China and become a prevalent strain. However, little is known about the unique antigenic sites of nVarIBDV escaped from current IBDV vaccines.MethodsHere, the expressed hypervariable region (HVR) of VP2 (VP2-HVR) of nVarIBDV was used as an immunogen and a novel monoclonal antibody (mAb) against VP2 (mAb 5B5) was generated.ResultsImmunofluorescence assay (IFA) and ELISA demonstrated that mAb 5B5 specifically reacted with nVarIBDV and its VP2 protein, but not with classical IBDV (cIBDV), very virulent IBDV (vvIBDV), or attenuated IBDV (attIBDV) strains. Epitope mapping and site mutagenesis assay revealed that mAb 5B5 recognized the conformational epitope in peak A (212–224 aa) and heptapeptide (326–332 aa) regions, and identified residue 221K in VP2 as the key antigenic site, which is conserved exclusively in nVarIBDV strains. Notably, K221Q mutation in VP2 of nVarIBDV significantly altered the reaction profile for sera against vvIBDV or cIBDV. Neutralization assays revealed that mAb 5B5 could inhibit replication of an engineered attIBDV carrying 221K in Leghorn male hepatoma (LMH) cells. Structural analysis further found that 221K is surface-exposed and alters local electrostatic potential, possibly facilitating immune evasion.DiscussionAll these demonstrated that 221K is a unique antigenic site in VP2 of nVarIBDV associated with immune escape, providing novel insights into the antigenicity of nVarIBDV and novel targets for efficient diagnostics, vaccine design, and molecular surveillance of IBDV.